PENGARUH GLOBALISASI INFORMASI TERHADAP KEHIDUPAN SOSIAL BUDAYA GENERASI MUDA ( SUATU STUDI DI SMA NEGERI 1 BEO KABUPATEN KEPULAUAN TALAUD ) - WABAA, MARTHA; LALOMA, ALDEN; LONDA, VERY (Sam Ratulangi University, 2014)
The population in the Talaud Islands, particularly in Beo nearly 90% are Christians.All people always respect one another. They always obey and follow the rules and / or norms, customsand respect among religions. This is reflected in the activities they do every day. Judging from thepeople who so respect the rules and customs applicable in everyday life, the inclusion of theglobalization of information and communication within a community of people who live in Beo,especially for the younger generation can cause a variety of problems, especially in the socio-culturalfield.Therefore the purpose of this study is to analyze the extent to which the impact ofglobalization of information on social and cultural life of the younger generation. This study took placein senior high school (SMA Negeri) 1 Beo Kepulauan Talaud. Design research is a quantitative studywith a sample of 60 respondents / students.The results showed that the opinions of students at SMAN 1 Beo Talaud information aboutthe impact of globalization, the average is still in the category of